Performance Evaluation of the Musi Emas Feeder City Transport, Palembang City - Ismail, Ayu; Kadarsah, Edi; Agustien, Melawaty (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
One aspect of transportation that concerns the lives of many people is public transportation. Public transportation is vital in people's lives, especially in urban areas, including Palembang. In line with the development of time, public transit in Palembang City continues to make updates, including the availability of Musi Emas feeder city transportation which serves seven corridors, and 2 of them are the Talang Kelapa - Punti Kayu corridor and the Hajj Dormitory - Semarang Borang with the application of buy the service. This study aims to analyze the performance of Musi Emas Palembang feeder city transportation. The type of research used is descriptive, with primary and secondary data sources. Performance evaluation is analyzed by comparing the findings in the field with Minimum Service Standard (SPM) regulations that apply to the parameters of travel time, travel speed, load factor, and headway time. The results showed that the travel time and speed performance met the minimum standards, while the load factor needed improvement. As for headway time, it can be more optimized.